Recent Advances in Dipeptidyl-Peptidase-4 Inhibition Therapy: Lessons from the Bench and Clinical Trials - Jixin Zhong; Quan Gong; Aditya Goud; Srividya Srinivasamaharaj; Sanjay Rajagopalan (Journal of Diabetes Research)
DPP4 inhibitors (DPP4i) are a class of newly developed antidiabetic drugs which preserve incretin hormones and promote postprandial insulin secretion. Although the cardiovascular effect of DPP4 inhibition has been substantially studied, the exact role of DPP4 in cardiovascular disease especially in humans remains elusive. Previous small studies and meta-analyses have suggested a benefit in both surrogate outcomes and cardiovascular events for these agents. However, there was growing evidence in recent years questioning the cardioprotective effect of DPP4i. Further, a signal of heart failure hospitalization in a recent large scale clinical trial SAVOR-TIMI 53 has called into question the safety of these agents and their utility in the treatment of cardiovascular disease. In this review, we will revisit the physiologic function of DPP4 and discuss its role in cardiometabolic disease based on recent experimental and clinical studies.